Pengaruh Ulir Pada Lubang Nozzle dan Karakteristik Api Pembakaran Berbahan Bakar Lpg - Anam, Muhamad Khoirul; Qiram, Ikhwanul; Adi Pratama Putra; Anas Mukhtar (Jurnal Teknik Mesin Indonesia, 2025)
Given Indonesia's growing population and economic development, the country is experiencing a greater need for fuel. There are now a number of alternative fuels available to lessen the ongoing need on fuel oil. One of the most affordable, cleaner, and readily available fuels worldwide is liquefied petroleum gas, or LPG. The geometric design of the burner, the flow dynamics contained in the non-premix flame flow structure and its function to stabilize the combustion process play an important role in the mixing process between fuel and air. The purpose of this research is to ascertain how nozzle thread changes affect the flame characteristics of burning LPG (liquified petroleum gas) fuel. In order to create an effective and efficient burner design, thread variations can be used to establish the properties of the diffusion combustion flame, such as flame stability and combustion temperature. Data collecting findings indicate that nozzles with threads have a greater temperature value than nozzles without threads. The proportion of.